Effect of Pretreatment on Microstructure and Mechanical Properties of Nafion™ XL Composite Membrane. Issue 5 (4th September 2019) - Lin, Q.; Sun, X.; Chen, X.; Shi, S.
Abstract: As an ion‐conductive polymer electrolyte, Nafion™ XL composite membrane is used to meet the requirement for cost reduction, performance and durability improvement in polymer electrolyte fuel cells. While significant durability is observed for Nafion™ XL membrane, the mechanisms of improved mechanical durability, especially the impact induced by pretreatment, is still left unexplored. In this paper, ex situ mechanical tests of pretreated membranes are carried out, including tensile, fracture and fatigue crack propagation tests, to unravel the complex interplay between strength, fracture toughness and cyclic hygrothermal stress that controls the mechanical durability. Pretreatment increases strain‐hardening modulus at the expense of reduced ductility, while the break stress is not affected. Results from in situ SEM tensile tests reveal that pretreatment increases the orientation resistance during tension, leading to increased stress responses. In addition, the fracture resistance and fatigue crack propagation resistance increase after pretreatment, which is ascribed to increased membrane stiffness and reinforcement fiber reorientation, respectively. From a microscopic point of view, fibers along the cross‐sectional reinforcement layer collapse, corresponding to fiber reorientation at a smaller size scale and accounting for the above increased resistance. The findings reported here will provide more insights into the mechanical durability of composite ion‐conductive membranes.